Dispute settlement reports 2019. Volume III, Pages 1099 to 1744 - World Trade Organization (Cambridge : Cambridge University Press, 2021)
These are the WTO's authorized and paginated reports in English. They are an essential addition to the library of all practising trade lawyers and a useful tool for students and academics worldwide working in the field of international economic or trade law. DSR 2019: Volume III contains the panel and Appellate Body reports on 'United States - Measures Concerning the Importation, Marketing and Sale of Tuna and Tuna Products (WT/DS381), Recourse to Article 21.5 of the DSU by the United States', 'Second Recourse to Article 21.5 of the DSU by Mexico'.
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: Foreign trade regulation -- Cases; Tariff -- Law and legislation -- Cases; Competition, Unfair -- Cases; Dispute resolution (Law) -- Cases